2001
DOI: 10.1007/s10434-001-0109-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Nodal Recurrence After Lymphadenectomy for Melanoma

Abstract: After ELND or TLND, patients who have a large tumor burden (thick primary melanoma, multiply involved lymph nodes, ECE), advanced age, and a primary lesion located in the head and neck have a significantly increased likelihood of relapse and a decreased survival. Few patients present with an isolated nodal recurrence, but the majority can be salvaged by a second dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Furthermore, many studies have identified high-risk features resulting in regional recurrence rates of 15-60% [7,69,[71][72][73][74][75] (Tables I and II). Regional recurrence is significantly associated with an increasing number of positive lymph nodes and extracapsular extension of melanoma [69,71,72]. Calabro et al noted a 9% risk of recurrence following lymphadenectomy with one positive lymph node against a 15-33% risk correlated to increasing number of positive nodes [69].…”
Section: Role Of Adjuvant Radiotherapymentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, many studies have identified high-risk features resulting in regional recurrence rates of 15-60% [7,69,[71][72][73][74][75] (Tables I and II). Regional recurrence is significantly associated with an increasing number of positive lymph nodes and extracapsular extension of melanoma [69,71,72]. Calabro et al noted a 9% risk of recurrence following lymphadenectomy with one positive lymph node against a 15-33% risk correlated to increasing number of positive nodes [69].…”
Section: Role Of Adjuvant Radiotherapymentioning
confidence: 97%
“…Similarly, an 18% recurrence rate was determined among 403 patients after axillary or inguinal lymphadenectomy in another large series [70]. Furthermore, many studies have identified high-risk features resulting in regional recurrence rates of 15-60% [7,69,[71][72][73][74][75] (Tables I and II). Regional recurrence is significantly associated with an increasing number of positive lymph nodes and extracapsular extension of melanoma [69,71,72].…”
Section: Role Of Adjuvant Radiotherapymentioning
confidence: 99%
“…[6][7][8][9] Also, some investigators have demonstrated that cervical location of nodal disease was itself an adverse prognostic factor, with associated rates of recurrence in the neck of 30% to 40%. 6,9,21 These data were compared with data reporting regional recurrence rates of approximately 10% when analyzing series of patients with these high-risk features who were treated with surgery followed by postoperative RT. 4,5 In our series of patients with simultaneous bilateral cervical metastases, the regional nodal control was only 64% at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that post-lymphadenectomy radiation should be considered in patients with these factors in order to reduce the risk of nodal recurrence [73,74]. Nodal recurrence is predictive of distant metastasis and poor survival [75]. Isolated nodal recurrence should be re-excised, and long term survival is possible in these patients [75,76].…”
Section: Nodal Dissection For Clinically Positive Nodesmentioning
confidence: 99%
“…Nodal recurrence is predictive of distant metastasis and poor survival [75]. Isolated nodal recurrence should be re-excised, and long term survival is possible in these patients [75,76].…”
Section: Nodal Dissection For Clinically Positive Nodesmentioning
confidence: 99%